Survei Persepsi Rekognisi Hak-Hak Sipil Siswa SMA di DKI Jakarta - Nasution, Maneger; Bunyamin, Bunyamin; Nawawi, Muhammad Azhar; Ruslan, Ahmad; Erlangga, Gery; Muhtarom, Herdin; Pratiwi, Ayu Kurnia (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This research is a study of the recognition of civil rights related to human values around tolerance, social solidarity, freedom, and responsibility. The purpose of this study is to find out how the perception of recognition of students' civil rights in DKI Jakarta. The research approach used in this study is quantitative. This study used a questionnaire data collection technique with a Likert scale model. The data analysis technique used in this study is a descriptive statistical analysis technique through percentage calculations. The results of this study show that the civil rights of students in the school environment have been recognized or upheld through the policies of educational institutions and in academic activities carried out in the school environment.